A risk calculator to predict suicide attempts among individuals with early‐onset bipolar disorder. (9th September 2022) - Goldstein, Tina R.; Merranko, John; Hafeman, Danella; Gill, Mary Kay; Liao, Fangzi; Sewall, Craig; Hower, Heather; Weinstock, Lauren; Yen, Shirley; Goldstein, Benjamin; Keller, Martin; Strober, Michael; et al.
Abstract: Objectives: To build a one‐year risk calculator (RC) to predict individualized risk for suicide attempt in early‐onset bipolar disorder. Methods: Youth numbering 394 with bipolar disorder who completed ≥2 follow‐up assessments (median follow‐up length = 13.1 years) in the longitudinal Course and Outcome of Bipolar Youth (COBY) study were included. Suicide attempt over follow‐up was assessed via the A‐LIFE Self‐Injurious/Suicidal Behavior scale. Predictors from the literature on suicidal behavior in bipolar disorder that are readily assessed in clinical practice were selected and trichotomized as appropriate (presence past 6 months/lifetime history only/no lifetime history). The RC was trained via boosted multinomial classification trees; predictions were calibrated via Platt scaling. Half of the sample was used to train, and the other half to independently test the RC. Results: There were 249 suicide attempts among 106 individuals. Ten predictors accounted for >90% of the cross‐validated relative influence in the model (AUC = 0.82; in order of relative influence): (1) age of mood disorder onset; (2) non‐suicidal self‐injurious behavior (trichotomized); (3) current age; (4) psychosis (trichotomized); (5) socioeconomic status; (6) most severe depressive symptoms in past 6 months (trichotomized none/subthreshold/threshold); (7) history of suicide attempt (trichotomized); (8) family history of suicidal behavior; (9) substance use disorder (trichotomized); (10) lifetime history of physical/sexual abuse. For all trichotomized variables, presence in the past 6 months reliably predicted higher risk than lifetime history. Conclusions: This RC holds promise as a clinical and research tool for prospective identification of individualized high‐risk periods for suicide attempt in early‐onset bipolar disorder.